Effect of Formulations and Spray Nozzles on 2, 4-D Spray Drift under Field Conditions. (28th May 2018) - Kalsing, Augusto; Rossi, Caio V. S.; Lucio, Felipe R.; Zobiole, Luiz H. S.; da Cunha, Luis C. V.; Minozzi, Guilherme B.
Abstract : Six trials were conducted during 2014/15 and 2015/16 growing seasons in Brazil to determine the effect of 2, 4-D formulations and spray nozzles on 2, 4-D spray drift under conventional field conditions. An experimental 2, 4-D choline formulation with Colex-D ® Technology (GF-3073) and a 2, 4-D dimethylamine (DMA) formulation were applied with either XR and AIXR flat-fan spray nozzles. Each plot was 30 m wide by 24 m long (720 m 2 ) with 60 glyphosate-resistant soybean rows spaced 50 cm apart and also 35 potted tomato plants distributed on a grid across the plot 5-m apart. Applications were performed one meter away from the plot edge perpendicular to the soybean rows when wind direction was parallel to the rows with less than 30 degrees of angle deviation. Spray drift treatments were applied in 100 L ha −1 with tractor sprayers at 276 kPa equipped with a 7-m wide boom at 50 cm above the canopy of the soybean plant, operating at 6.8 km h −1 . The distance from the plot edge to the farthest plant with 2, 4-D symptoms was assessed for every four soybean rows at 10 and 20 days after treatment (DAT) and potted tomatoes at 10 DAT. GF-3073 reduced the distance of the farthest injured plant with 2, 4-D symptoms compared to the 2, 4-D DMA formulation regardless of the spray nozzle, assessment date and sensitive species. GF-3073 applied through the AIXR nozzle reduced the relative drift affected area to the standard by 68% at 10 DAT and 67% at 20 DAT for soybean and 60% at 10 DAT for potted tomatoes.